2011
DOI: 10.1007/s00436-010-2154-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for giardiasis and soil-transmitted helminthiasis in three municipalities of Southeastern Minas Gerais State, Brazil

Abstract: Giardiasis and soil-transmitted helminthiasis (STH) are parasitic diseases that are among the major health concerns observed in economically disadvantaged populations of developing countries, and have clear social and environmental bases. In Brazil, there is a lack of epidemiologic data concerning these infections in the study area, whose inhabitants have plenty of access to health care services, including good dwelling and adequate sanitary conditions. In this survey we investigated the risk factors for giard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…Indeed, wealth, inadequate sewage discharge, drinking of unsafe water, lack of sanitary infrastructure, personal hygiene habits, recent travel history, low education and demographic factors are strongly associated with soil-transmitted helminth infections [42-46]. Our results show that GDP per capita has a negative effect on A. lumbricoides infection risk.…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, wealth, inadequate sewage discharge, drinking of unsafe water, lack of sanitary infrastructure, personal hygiene habits, recent travel history, low education and demographic factors are strongly associated with soil-transmitted helminth infections [42-46]. Our results show that GDP per capita has a negative effect on A. lumbricoides infection risk.…”
Section: Discussionmentioning
confidence: 79%
“…Chaudhary, et al [23], (from his study in Barabanki, Uttar Pradesh) also reported the peak prevalence of Giardia lamblia in the age group of 1-10 years (35.84%), which then declined gradually with successive increase in age reaching a least infectivity rate in the age group of 51-60 years (3.77%). Pinheiro et al [24], (from his study in Minas Gerais, Brazil) found that the children of below six years age are most susceptible to giardia infection, the infection rate then decreased in higher age groups with minimum infection rate in the age group of 15-24 years.…”
Section: Prevalence In Different Age Groupsmentioning
confidence: 99%
“…Previous research established a relationship between IPI presence and socioeconomic factors 8 : low maternal education level, low family income, living in a rural area, poor sanitary facilities and sewage systems and limited access to healthcare services were associated with a higher IPI prevalence [8][9][10][11] .…”
Section: Socio-economic Factorsmentioning
confidence: 99%
“…Approximately 44% of the population from Bogota is considered as being poor (SISBEN strata 1-2) 20 . Generally, the presence of IPIs is associated with living in a rural area because urban populations generally have better access to sanitation, clean water and health care services 11 . However, some researchers found the highest level of IPIs in peri-urban areas.…”
Section: Ipis In Colombiamentioning
confidence: 99%